Clinical Profile of Multiple Myeloma in South India - Fousad, Chemban; Gangadharan, K V; Abdulla, Mansoor C; Naryan, Ram; Mohammed, Ali (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: The incidence of multiple myeloma (MM) is known to be variable according to ethnicity and is increasing rapidly in Asian countries. Because of huge disparities in economy, lack of adequate health-care infrastructure and the lack of access to novel drugs in our country, treatment of multiple myeloma is still a challenge to medical field in India. Methods: This was a descriptive longitudinal study conducted in the medicine and oncology units of a tertiary care hospital in south India. During the one year period of data collection, 37 cases of multiple myeloma were diagnosed, of which 5 cases were excluded. The diagnosis of MM was made based on the International Myeloma Working Group: Criteria for the classification of monoclonal gammopathies, multiple myeloma and related disorders. The clinical and laboratory characteristics, and treatment were studied. Results: The male to female ratio was 1.3:1. The commonest symptoms noticed were fatigue 32 (100%) and bone pain 31 (96.9%). 6 (18.8%) patients had hypercalcemia and 7 (21.9%) patients had elevated serum creatinine levels. 29 (91%) of 32 had lytic lesions in the skull and 27 (84%) had lytic lesions in the spine. One patient expired during the course of the treatment. 20 (64%) of 32 patients had partial response to treatment, 7 (23%) had complete response and 4 (13%) of them had stable disease not responding to treatment. Conclusions: To conclude, the patients with multiple myeloma in the present study had a male preponderance. Most common symptoms noticed were fatigue and bone pain and majority had spine tenderness on examination. The presentation of MM is non-specific and patient can come with varied presentations at onset. The quality of life and survival in MM patients can be improved significantly if there is access to newer therapies.
Keywords: Clinical profile; multiple myeloma; South India